Low total cholesterol predicts early death in children with hemophagocytic lymphohistiocytosis - Xiao, Li; Xu, Ximing; Zhang, Zhiling; Dou, Ying; Guan, Xianmin; Guo, Yuxia; Yu, Jie (Frontiers in Pediatrics, 2023)
Background Hemophagocytic lymphohistiocytosis (HLH) is a rapidly progressive and potentially life-threatening disorder. Identifying risk factors and timely adjustment of the given treatment regimens is critical to reducing the early mortality in HLH patients. Hypocholesterolemia has been reported to be associated with poor prognosis in a variety of critical illnesses. However, serum cholesterol is rarely studied in HLH patients, and its prognostic value is unclear. Methods We conducted a retrospective cohort study in National Clinical Research Center for Child Health and Disorders (Chongqing), identifying pediatric HLH patients (including genetically confirmed pHLH and not genetically confirmed pHLH) diagnosed with the HLH-2004 protocol and treated with immunochemotherapy between January 2008 and December 2020. The patients' blood lipid levels at initial diagnosis of HLH, including triglycerides (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein-cholesterol (LDL-C), were reviewed based on electronic medical records. Both Cox and logistic regression models were used to estimate the effects of blood lipid indicators on early death (within 30 days after diagnosis). Results A total of 353 patients were enrolled in the study, with a median age at diagnosis of 45 months. The observed 30-day mortality rate was 19.05% (64/336, 17 were lost to follow-up) and Kaplan-Meier-estimated 3-year survival rate was 61.67% (95% CI, 56.27%–67.59%). DNA-targeted sequencing of HLH-related genes was performed in 173 (49.0%, 173/353) patients (not all patients with suspected pHLH underwent genetic testing), and 29 patients were diagnosed with genetically confirmed pHLH. Lipid panel was performed in 349 patients: 91.98% (321/349) had TG ≥ 1.80 mmol/L, 62.75%(219/349) had TG ≥ 3.00 mmol/L, 92.84% (324/349) had HDL-C ≤ 1.04 mmol/L, 58.74% (205/349) had LDL-C ≤ 1.30 mmol/L and 24.64% (86/349) had TC ≤ 3.11 mmol/L. TC ≤ 3.11 mmol/L and BUN ≥ 7.14 mmol/L were the independent risk factors for 30-day mortality [HR(95%CI): 2.85(1.46, 5.57) and 2.90(1.48, 5.68), respectively]. The presence of one of these risk factors increased the 30-day mortality rate by 6-fold [HR = 6.24, 95%CI: (3.18, 12.22)] and the presence of two risk factors by nearly 10-fold [HR = 9.98, 95%CI: (4.23, 23.56)] compared with the patients with no risk factors. Conclusion Severe derangement of lipoproteins is common in children with HLH, and decreased TC is an independent risk factor for early death. Hypocholesterolemia should be included as a biomarker during the diagnosis and management of HLH patients.